Teacher Stress in Primary Schools in One Education District in Trinidad and Tobago - Gowrie, George; Ramdass, Mala; Birbal, Ronald; Dass, Natasha; Singh, Vashti; Rocke, Judy (Advances in Social Sciences Research Journal, 2015)
The study explored teachers’ perceptions of the most common indicators of teachers’ stress in primary schools in the St. George East Education Division of Trinidad and Tobago. It sought, also, to develop separate teacher stress categories and make comparisons among schools. The sample consisted of randomly selected 219 teachers from a sample of government and government -assisted schools primary schools from the St. George Education taking into account variables such as size, school type, location, sex and years of teaching experience. The study examined the relationship between the school-level teacher stress factors as well as the predictive power of each independent factor on overall teachers’ stress. The study employed a quantitative method using a cross-sectional design. The data were analyzed using the Statistical Package for the Social Sciences (SPSS-SPG2). T-tests and ANOVA were used to examine teachers’ stress based on school type, location, sex and years of teaching experience. Correlation and regression analysis were employed to examine the relationship between each of the stress factors as well as their influence on the overall dependent teacher stress. The findings suggested that there were no significant differences in teacher stress based on school type and location, However, there were some significant differences in teachers stress based on age, sex and years of teaching experience on some stress factors Also, there was a high to moderate inter-correlation of the school level stress factors. Teacher workload and student behavior had the strongest relationship to overall teacher stress.